Sustainable financing strategies for SMEs: Two alternative models - Monzur Hossain; Naoyuki Yoshino; Kenmei Tsubota (Asian Development Bank Institute (ADBI), 2023)
A sustainable financing strategy for SMEs should aim to enhance a low-cost collateral-free supply of loans to SMEs with good track records of repayments to banks. This paper suggests two alternative financing mechanisms to overcome certain borrowing constraints of SMEs. First, it suggests an institutional mechanism involving the government, banks, and SMEs. Under the mechanism, a government's subsidized loan fund with the provision of training and capacity-building support to borrower SMEs could reduce, on the one hand, the fund constraint of banks and, on the other hand, the asymmetry of information about borrowers, and so does the default risks. This model will allow banks to offer collateral-free lower-interest credit to SMEs, thereby improving their access to finance and their performance as well. Second, as the first model might involve borrower selection bias and moral hazard problems, an alternative model has been proposed with a digital financing mechanism with/without subsidized funds that could produce similar or better results. Using survey data from 526 SMEs in Bangladesh, the empirical results are found to be consistent with the prediction of our theoretical model.
Keywords: O16; L25; 330; SME financing models; credit wholesale program; default risk; digital finance; Bangladesh